Organ donation after medically assisted death on psychiatric grounds: an ethical analysis - van Vlerken, Karlijn; Marijnissen, Radboud; Pronk, Rosalie; Widdershoven, Guy; van Veen, Sisco (Frontiers in Psychiatry, 2025)
Organ donation after medical assistance in dying (MAID) on psychiatric grounds is a relatively new practice that poses complex ethical challenges. This paper explores several ethical issues that are important for guiding current and future practice. While organ donation after MAID may alleviate organ shortages, it also prompts concerns regarding the instrumentalization of human life. However, it can be argued that if a patient wishes to donate, based on insight and deliberation, the person is not just regarded as a means. This implies that decision-making capacity is crucial, which requires considering the potential influence of psychiatric disorders. A further issue that can compromise decision-making is susceptibility to external pressures. Careful assessment of the patient’s decision-making capacity and the absence of external pressure are needed to avoid the stigmatization of individuals with psychiatric conditions. Further research to better understand the possible interplay between psychiatric disorders and decision-making capacity in the context of organ donation after MAID is recommended.